Is Dietary Knowledge a need of final-year medical undergraduates for better clinicians in future? - Muhammad Omar Ahmad, Zahid Hafeez, Usama Tariq, Saqib Rashid, Muhammad Muneeb, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: A healthy diet is essential for good health and nutrition. Health professionals are considered role models in promoting healthy diet patterns. However, in a few studies, it was evident that most physicians have inadequate training in dietary knowledge to guide patients, although final-year students have better knowledge than first-year students, which shows nutrition care improved with progression through their medical training. Aim: To assess the dietary knowledge of final-year medical students and to assess their attitudes toward the importance of dietary counseling as practicing physicians in the future. Methodology: A cross-sectional study was conducted at Shalamar Medical and Dental College, Lahore, on final-year MBBS students of Shalamar Medical and Dental College. After the approval of SMDC-IRB (IRB-197), data was collected in the form of study proforma by the final-year students of SMDC using their WhatsApp contacts. Those who responded were considered participants in the study, while those who did not respond after the second reminder were considered excluded from the study. Statistical analysis was done using the SPSS package version 20.0. To access differences in means of quantitative variables, independent samples t-tests and one-way ANOVA tests were applied. The correlation was analyzed by the Pearson correlation coefficient. The statistical methods were verified, assuming a significance level of p < 0.05 and a highly significant level of p<0.001. The total score for knowledge, attitude, and practice was categorized as good/positive or poor/negative based on a 75% cut-off point out of the total expected score for each. Results: The 134 students participated in the study. Male students were found to be more overweight or obese compared to female students (p<0.025). M The majority of students rated their self-reported health as good. To explore the knowledge, responses to questions related to cardiovascular problems, diabetes, respiratory diseases, gastrointestinal diseases, and anemia were recorded. Almost three-fourths of the students were aware of the major health issues. According to 773% of students, iron present in meat is a better source of iron compared to vegetables. A similar response was found for gluten-rich diets. More than 90% of the students considered dietary knowledge an essential component for better clinical care of the patient. Conclusion: Final-year MBBS students, though adequately trained, consider that having additional dietary knowledge can help them in counseling patients about diet. Keywords: Nutrition, diet intake, food knowledge, medical education, medical students